Pluripotency markers are differentially induced by IGF1 and bFGF in cells from patients' lesions of large/giant congenital melanocytic nevi - Dipanjan Basu; Cláudia M. Salgado; Janki R. Patel; Joie Zabec; Ryan M. Hoehl; Bruce Bauer; Miguel Reyes-Múgica (BMC, 2019)
Abstract Factors regulating transcription of pluripotency genes in congenital nevo-melanocytes are not known. Nevo-melanocytes belong somewhere in-between the ends of a spectrum where the normal epidermal melanocyte represents one end and a melanoma cell with multiple genetic abnormalities represents the other. Cells from large/giant congenital nevi (L/GCMN), unlike normal melanocytes, grow colonies on soft agar and express pluripotency markers, similar to melanoma cells. In this study normal melanocytes, SKMEL28 melanoma cells and nevo-melanocytes isolated from three L/GCMN patients were exposed to niche factors bFGF and IGF1 in vitro at physiological doses, and expression of a panel of pluripotency markers was determined by RT-PCR. While normal melanocytes did not show any significant transcriptional change in the genes studied, bFGF induced transcription of Sox2 and Bmi1 in melanoma cells. Patients' cells showed differential expression, with Sox10 being common to C76N and PD1N, while only Sox2 and Bmi1 were upregulated in C139N. IGF1 on the other hand induced unique sets of genes in each individual sample. We conclude that expression of pluripotency genes in L/GCMN cells is affected by niche factors bFGF and IGF1; however, each individual growth factor induced a unique set of genes in a patient's cells.